PASSIVE TRANSITIVE SENTENCES FROM VIEWPOINT OF TRANSITIVITY AND COGNITION - Dương Hữu Biên (Tạp chí Khoa học Đại học Đà Lạt)
This paper is on passive transitive sentences - a topic that many scholars have discussed - in a different perspective. Specifically, this paper discusses the passive transitive sentences within the participant structure, semantic structure roles of transitive sentences and these roles are associated with their cognitive prominence. Through this cognitive prominence, the paper shows that foregrounding this role or other roles in the passive transitives is motivated cognitively. This is a universal feature of human thoughts.